(3GdZQjHjfs - (3CMeO Hf eMeO Hf YHO GdQMef GdHGTGfj GdgQhj, CHh YHjO, J (B401 (3g` s ((3eUQ s)
(3ChdgG (B:s
(3jHOC HHGH GdYjf eY Gdeje s
(3BNQgG (B:s
(3jfJgi HHGH GdbGa eY GdYjf s
(3GdfSNI HgG MhGTs
(3Ydjg SeGYGJ cKjQI LOkG ai GdbQfjf GdSGOS hGdSGHYs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B210s
Keywords: (3GdMOjK h GdeUWdMs